The Role of Cognitive Skills, Non-Cognitive Skills, and Internet Use on Entrepreneurs’ Success in Indonesia - Lia Gustina; Diah Ayu Utami; Padang Wicaksono (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2020)
Abstract: This study aims to analyze the effect of cognitive skills, non-cognitive skills, and internet use on the entrepreneur's success in Indonesia. Using the Indonesian Family Life Survey (IFLS) conducted in 2014 (IFLS-5), this study observed people of 15-64 years old who work as entrepreneurs which amounted to 4.111 observations. The model used is Ordinary Least Square (OLS) Regression. The results showed that cognitive and non-cognitive skills will determine the entrepreneur's success by profit measure. The higher the cognitive and non-cognitive skills possessed by the entrepreneur, the higher the profit obtained. Entrepreneurs who use the internet will also get higher profits than entrepreneurs who do not use the internet. In addition, the profit earned by the entrepreneur will be even higher if: age increases, of male sex, is highly educated and is living in urban areas. Keywords: Entrepreneur, Cognitive Skills, Non-Cognitive Skills, Internet, OLS Peran Kemampuan Kognitif dan Nonkognitif serta Penggunaan Internet terhadap Kesuksesan Wirausaha di Indonesia Abstrak: Penelitian ini bertujuan untuk mengetahui peranan variabel kemampuan kognitif, kemampuan nonkognitif, dan penggunaan internet terhadap kesuksesan seorang wirausaha. Data yang digunakan bersumber dari Indonesian Family Life Survey (IFLS) tahun 2014 (IFLS-5) dan unit analisisnya adalah individu usia 15-64 tahun yang bekerja sebagai wirausaha dengan observasi berjumlah 4.111 individu. Metode yang digunakan adalah Ordinary Least Square (OLS) Regression. Hasil penelitian menunjukkan bahwa kemampuan kognitif dan nonkognitif akan menentukan kesuksesan wirausaha yang diukur dengan profit yang diperoleh. Semakin tinggi kemampuan kognitif dan nonkognitif yang dimiliki wirausaha menunjukkan profit yang diperoleh semakin tinggi. Wirausaha yang menggunakan internet juga akan memperoleh profit yang lebih tinggi dibanding wirausaha yang tidak menggunakan internet. Selain itu, profit yang diperoleh wirausaha akan semakin tinggi jika: usia semakin bertambah, berjenis kelamin laki-laki, berpendidikan tinggi (SMA ke atas), dan tinggal di daerah perkotaan. Kata kunci: Wirausaha, Kemampuan Kognitif, Kemampuan Nonkognitif, Internet, OLS